Prevention of traumatic brain injury complications in sports - A. V. Smolenskiy; O. A. Shevelev; M. V. Petrova; M. Yu. Yuryev; E. O. Sheveleva; A. V. Tarasov; A. B. Miroshnikov (National Electronic Information Consortium (NEICON), 2022)
The aim of the review is to inform doctors and trainers of sports teams about technologies that prevent complications of sport brain injuries (SBI). Low levels of visibility of clinical manifestations, specific characteristics of individual reactions to injury, anti-aggravation behavior among sportsmen, absence of unbiased methods of diagnostics of SBI are the main reasons behind underestimation of the severity of trauma. Treatment and rehabilitation procedures of mild SBI do not currently consider specific characteristics of trauma, associated with the increase in body and brain temperature and reduced cerebral perfusion during the traumatizing intervention. Injury of the brain causes an increase in cerebral temperature, which, in turn, can aggravate the consequences of traumatization. The control of the temperature of the brain can be achieved with non-invasive method of microwave radiometry, while the technology of craniocerebral hypothermia (CCH), which has evident neuroprotective properties, can aid in the prevention of complications of SBI.